Bauran Pemasaran Pada BMT Mandiri Sejahtera Cabang Kedungpring Dalam Prespektif Etika Bisnis Islam - Hidayat, Moch Amrizal; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2019)
The problem of economic development in the last two decades is the problem of financial institutions that have not applied Islamic business ethics. amidst the current tight competition of sharia institutions which are one of the sharia financial institutions that maintain existence in society through the attention of members and always provide excellent service to members are BMT (Baitul Maal Wat Tamwil), using the marketing mix in accordance with ethics Islamic business is one way that is used to attract members through marketing by using the whole system of marketing activities that are in accordance with Islamic Sharia. This research is a qualitative research that aims to determine the implementation of the marketing mix at the Kedungpring Branch of Mandiri Sejahtera BMT in the perspective of Islamic business ethics. From the results of the research that has been done, it can be concluded that in implementing the marketing mix in terms of products, prices, places, promotions, people, processes, physical evidence, promises, patience applied to the Mandiri BMT Kedungpring Branch is in accordance with Islamic Shari’a ie applying the rules Islamic business such as marketing good quality goods, prohibiting pledges, being kind, creating good ties with members.